VIEWS AND PUBLIC POLITICAL ACTIVITIES OF STANISŁAW STEMPOWSKI DURING THE YEARS OF THE UKRAINIAN NATIONAL REVOLUTION. 1917 – 1921. - BILOBROVETS, Olga (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the article is to present and analyze the public views and public political activity of one of the leaders of the Polish democratic camp in Ukraine, Stanisław Stempowski, to clarify his place and role in the public political life of Ukraine during the Ukrainian National Revolution and state formation. The research methodology is based on the principles of historicism, systematicity and objectivity. Owing to the chronological method and historical political and proposographical analysis, the policy of the Polish democratic camp in Ukraine in relation to the Ukrainian statehood has been elucidated through the position of its leader. The scientific novelty consists in presenting the public views and public political activities of the Polish democrat Stanisław Stempowski in the events of the Ukrainian National Revolution and the Ukrainian and Polish state formation in the first decades of the 20th century. Conclusions. Stanisław Stempowski, a Polish landowner from Podillia, belonged to the Polish democratic camp in Ukraine and was a consistent supporter of the Ukrainian state independence. From his childhood, he developed friendship and respect for the Ukrainian people and recepted the Ukrainians as the masters of their land during the revolutionary and democratic transformations of 1917. After becoming the leader of the party of the democratic camp in Ukraine – the Polish Democratic Central, which united the majority of Polish democratic groups, he held struggle with the Polish nationalists (National Democrats, Endeks), defended the autonomy and interests of the Polish population in Ukraine. The Polish democratic camp supported the Ukrainian statehood, cooperated with the Ukrainian Central Council at various stages of statehood. As Minister of Land Affairs and Health and Social Welfare in two governments of the Ukrainian People's Republic, Stanisław Stempowski contributed to the development of the Ukrainian state. An extraordinary personality, intellectual, translator, freemason, social and political figure with a vivid democratic and civic position, Stanisław Stempowski left his bright mark in the Ukrainian and Polish history. Key words: Stanisław Stempowski, the Polish democratic camp in Ukraine, the Ukrainian National Revolution, public views, public and political activity.